Bitcoin and Blockchain: A Threat or Opportunity for the Financial System - ATICI, Gonca (European Journal of Economics and Business Studies, 2018)
As world economy evolved over years, barter which is a primitive transaction system left its place to money system. Commodity and bimetallic systems of money resolved the problems, especially the requirement of double coincidence of wants and eased the trade within parties. Chronologically, paper system of money followed the commodity system and implemented via two methods. In the first method, convertible paper money is converted into gold and silver by the authority that issued paper money. In the second method that is still valid today, fiat money is accepted by parties because of its being a legal tender. Money supply definitions keep changing as new liquid assets emerge day by day. Especially after the post global financial crisis, central banks have a more critical function for the world economies. Keeping all these developments aside, surrounded by fintech trends, financial system has confronted with a new instrument bitcoin that is first introduced in 2009. Though there are still too many consideration about this new financial instrument, number of bitcoins has growing since 2009 and has reached almost 17 million as of September 2018. Some economists consider bitcoin and other cryptocurrencies as a threat especially for central banks’ emission power. In this study we try to shed light to bitcoin, other cryptocurrencies and blockchain technology with regard to their evolvement and whether they pose a threat or provide an opportunity to the financial system.